2014
DOI: 10.1007/s11695-014-1314-y
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life, Weight Loss and Improvement of Co-morbidities After Primary and Revisional Laparoscopic Roux Y Gastric Bypass Procedure—Comparative Match Pair Study

Abstract: Revisional LRYGB is an effective and safe method for patients with inadequate weight loss after previous bariatric surgery concerning weight reduction, life quality and improvement of co-morbidities. Our results indicate lower efficacy of revisional compared to primary LRYGB reaching statistical significance in regard to weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
3
8
1
Order By: Relevance
“…In terms of anthropometric parameters, some studies have not observed differences in EWL% between patients who received P-RYGB and R-RYGB [12,13]. Conversely, patients who underwent P-RYGB have been reported to achieve significantly better EWL% [16,18], consistent with the findings of the current study. Likewise, the patients who received P-RYGB in our study had a significantly higher TWL% than patients who received R-RYGB, similar to the findings from other studies [20,28].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In terms of anthropometric parameters, some studies have not observed differences in EWL% between patients who received P-RYGB and R-RYGB [12,13]. Conversely, patients who underwent P-RYGB have been reported to achieve significantly better EWL% [16,18], consistent with the findings of the current study. Likewise, the patients who received P-RYGB in our study had a significantly higher TWL% than patients who received R-RYGB, similar to the findings from other studies [20,28].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, these studies reported inconsistent findings, suggesting comparable weight loss and complications for patients who underwent P-RYGB and R-RYGB [12][13][14] or inferior weight loss and higher complications in patients who received R-RYGB [15,16]. Furthermore, few studies have assessed the evolution of comorbidities after P-RYGB and R-RYGB [8,17,18], despite the possibility of relapse of comorbidities after RYGB (e.g., T2DM, HTN, and dyslipidemia). Likewise, studies comparing P-RYGB to R-RYGB only reported the remission of the comorbidities, with no data provided on the improvements or relapses [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Some surgeons [1,9] have suggested that a restrictive procedure needing conversion for inadequate weight loss should preferably be converted to one that also provides a degree of malabsorption. Elnahas et al [1] demonstrated superior outcome with revisional RYGB and bilio-pancreatic diversion (BPD)/DS for converting a gastric band in their systematic review of revisional surgery after failed AGB; weight loss was not sustained in the SG group.…”
Section: Discussionmentioning
confidence: 99%
“…Risks as well as the benefits with RBS depend on the nature of primary [2,6] as well as the secondary procedure. For example, revisions of adjustable gastric banding (AGB) and sleeve gastrectomy (SG) carry fewer risks than revisions from vertical banded gastroplasty (VBG), horizontal gastroplasty, and Roux-en-Y gastric bypass (RYGB) [2,3,6,7,9,10]. Similarly, a revision to RYGB carries lower risks than revision to duodenal switch (DS) and higher risks than revision to SG [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation